Amplified spontaneous emission in insulated polythiophenes. Issue 24 (13th June 2018) - Sun, Chen; Mróz, Marta Magdalena; Castro Smirnov, José Raúl; Lüer, Larry; Hermida-Merino, Daniel; Zhao, Chunhui; Takeuchi, Masayuki; Sugiyasu, Kazunori; Cabanillas-González, Juan
Abstract : Insulated polythiophenes bearing conjugated backbones that are fully (IPT) or half (½IPT) encapsulated are investigated to determine the relationship between their structure, photophysics and light amplifying properties. Abstract : Insulated polythiophenes bearing conjugated backbones, which are fully (IPT) or half (½IPT) encapsulated by cyclic side chains (IPTs), are introduced and comprehensively investigated to determine the relationship between their structure, photophysics and light-amplifying properties in the solid state. Upon full polythiophene encapsulation, we observe enhanced planarization of the conjugated backbone, which is demonstrated by the highly vibronic and mirror-image absorption and photoluminescence spectra in solution and solid state. In sharp contrast with poly(3-hexylthiophene) (P3HT), ½IPT and IPT exhibit a progressive reduction in torsional relaxation in solution together with significantly larger photoluminescence quantum efficiencies. The transient absorption (TA) spectra of ½IPT and IPT in the solid state depict clear stimulated emission (SE) bands free of spectral overlap with photoinduced absorption (PA) from inter-chain charge pairs. Furthermore, effective solid state backbone encapsulation is reflected in high SE cross-sections and efficient amplified spontaneous emission in 1/2IPT and IPT. Our results show that backbone self-sheathing enables the exploitation of single chain properties in the solid state, which is of particular relevance for lighting applications.